Sulfonation of Polyethylene Improves Functionality for Fabricating Technical Textiles - Mohib Reza, Kazimi; C. K. M., Faizal; Saidatul Shima, Jamari; Tahir, Shah; Mumtaz D., Naqvi (Society of Plastics Engineers, 2014)
Incorporating conductive nanoﬁbers into a polymer composite, so that it carries electrical signals and possesses hydrophilic properties similar to nylon and polyester, is a promising and potentially economically viable approach to new textiles. The matrix material will still constitute more than 90% of such a composite system. Thus it is very important for the matrix to interact with the ﬁllers in order to augment the desired functional properties. Low-density polyethylene (LDPE) possesses good mechanical, thermal, and chemical properties, well suited to making products. However, its low surface energy values are problematic for making a product with hydrophilic and electrical properties. Introducing functional group moieties could not only make the polymer more hydrophilic and conductive, it could also make LDPE more receptive to nanoﬁllers.